PENGARUH MEDIA SOSIAL TERHADAP PRESTASI BELAJAR TARUNA POLITEKNIK ILMU PEMASYARAKATAN - Karimah Aini; Kusmiyanti Kusmiyanti (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2021)
This study aims to see the effect of the use of social media on the academic achievement of cadets at the Correctional Sciences Polytechnic, especially the Correctional Management study program. The research method uses a quantitative approach. The population used in this study were all cadets of the Correctional Management study program Force 53 as many as 101 cadets with a research sample of 81 cadets selected through simple random sampling technique. . The data collection method used is by distributing online questionnaires to the cadets. The data analysis technique used is simple linear regression analysis using SBM SPSS 23. The results show that there is a strong positive influence between the use of social media and the cadets' learning achievement seen from the results of the determination test where the R value as the correlation coefficient is 0.754 0,5. From the results of simple linear regression analysis, it is stated that the regression coefficient of the Social Media variable (X) is 13,587 which means that for every 1% increase in the value of the Social Media variable, the learning achievement variable (Y) will increase by 0.560X. Because the nature of the regression is directly proportional, it can be seen that the greater the influence of social media, the learning achievement will increase. In conclusion, social media has an influence on cadets' learning achievement.